PENGARUH PENERAPAN E-FILLING, PEMAHAMAN PERPAJAKAN DAN PREFERENSI RISIKO WAJIB PAJAK TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI PADA KPP PRATAMAMEDAN TIMUR - Ira Inggi Wibowo; Sri Fitria Jayusman (Program Studi Akuntansi Fakultas Ekonomi UMN AL Washliyah, 2023)
Taxpayers have a role in the tax collection system and greatly determine the achievement of tax revenue targets. This research aims to analyze the effect of implementing e-filing, understanding taxation and taxpayer risk preferences on individual taxpayer (WPOP) compliance. This research is a type of quantitative research that is causal associative in nature using survey methods. The research sample was 100 WPOP at KPP Pratama Medan Timur. Research data was collected using a questionnaire. The data analysis technique uses multiple linear regression analysis with the help of the SPSS program. The research results concluded that: (1) the implementation of e-filing has a positive and significant effect on taxpayer compliance; (2) understanding taxation has a positive and significant effect on taxpayer compliance; (3) taxpayer risk preferences have a positive and significant effect on taxpayer compliance; and (4) the implementation of e-filing, understanding taxation and taxpayer risk preferences simultaneously have a positive and significant effect on individual taxpayer compliance at KPP Pratama Medan Timur. The contribution or influence of the variables implementing e-filing, understanding taxation and risk preferences on individual taxpayer compliance is 43.9%, while the remaining 56.1% is explained by factors or variables other than the variables proposed in this research.